Running on empty: anaemia in the elderly. - Chalmers, Leanne; Peterson, G. (Pharmaceutical Society of Australia, 2012)
Mrs K, a 72-year-old woman with a history of rheumatoid arthritis, reported gradual worsening of symptoms over the past two months, with fatigue and increased stiffness of the wrists and joints of the hands. Her primary therapy for rheumatoid arthritis was methotrexate 7.5 mg once-weekly. She rarely took non-steroidal anti-inflammatory drugs. Her haemoglobin level had dropped from 12.5 g/dL to 9.2 g/dL (12-16 g/dL) over the past three months. Her serum ferritin was 120 mug/L (15-300 mug/L).